2014
DOI: 10.1186/1471-2334-14-496
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of cytopenias in HIV-infected adults initiating highly active antiretroviral therapy in Uganda

Abstract: BackgroundCytopenias are the most common HIV-associated hematological abnormality. Cytopenias have been associated with several factors including sex, race/ethnicity, geographical location and comorbidities such as tuberculosis, hepatitis B infection, fever and oral candidiasis. Cytopenias become more prevalent as HIV progresses and are often fatal. Data from resource-limited settings about the prevalence and correlates of cytopenia are limited. Therefore we conducted this cross-sectional study to assess the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

30
78
8
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(122 citation statements)
references
References 45 publications
30
78
8
6
Order By: Relevance
“…Lower BMI is related to malnutrition and nutrient deficiencies, including deficiencies of vitamin B12, folate, and iron, which directly result in anemia. Similar to prior findings (3,20), our results found a strong independent association between CD4 count ≤ 199 × 10 9 /L and anemia; this association was most pronounced in those with a CD4 count < 50 × 10 9 /L. We also demonstrated that higher baseline HIV viral loads were associated with anemia.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Lower BMI is related to malnutrition and nutrient deficiencies, including deficiencies of vitamin B12, folate, and iron, which directly result in anemia. Similar to prior findings (3,20), our results found a strong independent association between CD4 count ≤ 199 × 10 9 /L and anemia; this association was most pronounced in those with a CD4 count < 50 × 10 9 /L. We also demonstrated that higher baseline HIV viral loads were associated with anemia.…”
Section: Discussionsupporting
confidence: 80%
“…The guidelines for the use of antiretroviral agents in China (25) recommend initiation of cART at a CD4 count < 350 × 10 9 /L, or a CD4 count > 350 × 10 9 /L certain clinical criteria are met. Some studies documented that a CD4 count < 200 × 10 9 /L was associated with myelosuppression and anemia (20). Thus, initiating cART at a higher CD4 count threshold reduces the risk of anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, this was an observational study, we were able to examine potential associations but were not able to assess causation, so it is not clear if the cytopenias preceded the HIV infection or vice versa. Third, cytopenias are associated with several factors including geographical location and comorbidities such as tuberculosis, hepatitis B infection, fever and oral candidiasis (15), these factors were not assessed in our study. Therefore, we were not able to determine the association between these factors and the prevalence of cytopenias.…”
Section: Discussionmentioning
confidence: 92%
“…Leukopenia and thrombocytopenia were seen in 26.8% and 21.7% of HIV patients with CD4 counts less than 200 cells/mm 3 in India, respectively (14). Leukopenia and thrombocytopenia occurred in 24.3% and 8.3% of adult AIDS patients at initiation of ART in Uganda, respectively (15). The study in Uganda showed that the presence of any cytopenia was associated with female sex, decreasing CD4 count and decreasing body mass index.…”
Section: Discussionmentioning
confidence: 92%